PEMASARAN KEPITING BAKAU SECARA TRADISIONAL OLEH MASYARAKAT KAMPUNG SAYOLO DISTRIK TEMINABUAN KABUPATEN SORONG SELATAN - Hendry Jems Yoel Aidore; Anna Dara; Krisna Fransina Lermating; Sri Anggasari Makatita (Jurnal Administrasi Terapan, 2023)
This research aims to determine the marketing channels for mud crabs and the level of prices, costs and income of mud crab fishermen in Sayolo Village, Teminabuan District, South Sorong Regency. The research was carried out using observation and interview methods which were carried out in June-September 2023 in Sayolo village with two sample Neighborhood Units. Each sample involved one mud crab fishing entrepreneur. Primary data is data obtained from in-depth interviews with mangrove crab fishermen respondents using a questionnaire (list of questions). In this research, there are two types of marketing channels for mud crab fishing entrepreneurs in Sayolo Village, Teminabuan District, namely the first type, producers sell mud crabs to final consumers, the second type, producers sell mud crabs to district traders, sell mud crabs to traders outside the district, sell to final consumers. The price of mangrove crabs at the fishermen's market level is IDR 20,000/bin with an average gross income of IDR. 537,500/person, while fishermen sell mud crabs to holding traders for small Bs Rp. 10,000, Large Bs Rp. 30,000, Up medium size Rp. 40,0000 and up to a large size of Rp. 60,0000 with an average gross income received of Rp. 809,000/person. The costs incurred by mangrove crab fishing entrepreneurs are based on two neighborhood units in Sayolo Village, namely Sayolo (RT 1) with an average total cost of Rp. 493,037.50/org, and Sayolo 2 (RT 2) with an average total cost of Rp. 747,103.57/org. The income of mud crab fishing entrepreneurs in Sayolo Village, Teminabuan District is classified as very low compared to the minimum wage of Southwest Papua Province, thus the highest income is made by mud crab fishing entrepreneurs from Sayolo 1 (RT 1) with an average income of IDR 531,296/person, followed by Sayolo 2 (RT 2) with an average income of Rp. 426.110/org Keywords: Mud Crab, Mud Crab Marketing, Costs, Income, Sayolo Village.